MARKET VALUATION AS A MODERATOR OF INVESTMENT RISK AND INVESTMENT OPPORTUNITY SET ON STOCK RETURNS - Evi Veronika Dewi; Siti Nurul Fathimah (Jurnal Ekonomi dan Manajemen, 2026)
This study investigates the effect of investment risk and the Investment Opportunity Set (IOS) on stock returns, with market valuation examined as a moderating variable. The analysis employs panel data from companies included in the Kompas 100 Index over the 2018–2022 period and applies a Random Effect Model (REM) within a Moderated Regression Analysis (MRA) framework. The results reveal that investment risk has a negative and statistically significant effect on stock returns, indicating that higher risk levels tend to reduce realized returns in the Indonesian capital market. Conversely, the Investment Opportunity Set (IOS) exerts a positive and significant influence on stock returns, suggesting that firms with stronger growth prospects are more attractive to investors. Market valuation, however, does not significantly affect stock returns and does not moderate the relationship between investment risk and stock returns or between IOS and stock returns. These findings indicate that market valuation acts as an independent variable rather than a moderating factor. Overall, the study highlights the importance of firm-specific fundamentals in explaining stock return behavior in emerging markets.